2014 Second IEEE Working Conference on Software Visualization 2014
DOI: 10.1109/vissoft.2014.30
|View full text |Cite
|
Sign up to set email alerts
|

AniMatrix: A Matrix-Based Visualization of Software Evolution

Abstract: Software designs are ever changing to adapt to new environments and requirements. Tracking and understanding changes in modules and relationships in a software project is difficult, but even more so when the software goes through several types of changes. The typical complexity and size of software also makes it harder to grasp software evolution patterns. In this paper, we present an interactive matrix-based visualization technique that, combined with animation, depicts how software designs evolve. For exampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…In addition to execution, another dynamic aspect of software that can be visualized is its evolution—the changes applied to software systems over time: for instance, the evolution of call, inheritance or flow graphs [CKN*03], of co‐changed files [BH06], or author–file relationships [OM08, OM09]. Evolution patterns, as described by Rufiange and Melançon [RM14], can be detected with those visualizations. Hence, software systems have different dimensions of time—execution and evolution—and relevant graph data can be derived and combined from multiple sources.…”
Section: Applicationmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to execution, another dynamic aspect of software that can be visualized is its evolution—the changes applied to software systems over time: for instance, the evolution of call, inheritance or flow graphs [CKN*03], of co‐changed files [BH06], or author–file relationships [OM08, OM09]. Evolution patterns, as described by Rufiange and Melançon [RM14], can be detected with those visualizations. Hence, software systems have different dimensions of time—execution and evolution—and relevant graph data can be derived and combined from multiple sources.…”
Section: Applicationmentioning
confidence: 99%
“…While not all combinations are sensible, there are a number of hybrid variants that appear to be promising: for instance, the combination of node‐link diagrams and matrices have already been successfully explored for static graphs [HF07, HFM07]. Recently, it has been shown that animating a matrix diagram also works if the animation process is designed with similar care as in those works describing the transition problem for node‐link diagrams (Taxonomy Category I.a.3) [RM14]. Further, combinations of animation and timeline approaches have not yet been fully explored.…”
Section: Research Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…To show temporal evolution of networks, most commonly a series of diagrams gets animated or is shown next to each other as small multiples (Archambault et al 2014;Beck et al 2014). Rufiange and Melançon's (2014) taxonomy of dynamic networks includes glyphs that show small summaries of the evolution of edges. They propose extended glyphs for the visualisation of multivariate edges (e.g.…”
Section: Visualisation Of Temporal Evolutionmentioning
confidence: 99%
“…Where the former concentrates on streets and buildings on their sides, the latter is more similar to the software maps used in this paper. A matrix-based approach supported by animated transitions named AniMatrix supports in understanding the evolution of source code entities and their dependencies (Rufiange and Melançon, 2014). Caserta et.…”
Section: Visualization Of Software and Its Evolutionmentioning
confidence: 99%